THE OBSTACLES TEACHERS FACE IN INCREASING DISCIPLINE CHARACTER AT SD NEGERI 173553 SIMAREMARE JAE - Santy Siahaan; Lastri Manurung (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2025)
Every teacher faces challenges in maintaining discipline and students' character, which can affect the effectiveness of teaching and learning in the class. This study deepens the obstacles educators encounter while facing student character and student indiscipline. Teachers will implement an effective learning system and refer to the teacher himself by carrying out a role that can build student discipline and character, utilizing a qualitative approach, by distributing questionnaires to teachers and students at the elementary school level, where elementary school education is the most basic education. So, the challenge teachers face is how teachers can shape students' character according to the basis of education in Indonesia. Teachers must be able to play a role in all fields, facilitators, motivators, inspirators, etc., because the teacher's attitude and behavior are real examples that are easy for students to imitate. This study can refer to how a teacher changes strategy to improve and build disciplined character in students.